Допуск як структура - Чайковська, Є. (Видавництво Національного університету “Львівська політехніка”, 2004)
Sinergetic concept of the diagnostics of the energy systems is designed. Motivation of the tolerance as information, ranked, space-time structure is presented.
Keywords: 621.182.2.001.57